Muck Improvement Technology for Connection Passage of Shield Tunneling Metro Tunnels in Coastal Areas - JIANG Peng; ZHANG Chong; LI Gang; DONG Zibo; DENG Yuebao; ZHU Yaohong (Chengshi guidao jiaotong yanjiu)
［Objective］ In the process of the earth pressure balance shield machine advancing in the coastal area cohesive soil layer, phenomena such as mud cake formation, unsmooth muck discharge, and blockage of the soil chamber often occur. In order to meet the requirements of shield tunneling, it is necessary to study the muck improvement technology in the cohesive soil layer. ［Method］ Based on a silty clay shield tunneling project of the connection passage on Ningbo Metro Line 5, the optimal mass fraction and the best injection ratio of the foaming agent are determined through the muck improvement test. The test results are applied to the shield tunneling construction site of the connection passage to verify the reliability of the improvement technology. The finite element method is used to analyze the influence of shield tunneling construction on the deformation of the soil layer at the site before and after the muck improvement. ［Result & Conclusion］ The optimal mass fraction and the best injection ratio of the foaming agent are determined to be 3% and 20% respectively through tests. The test results are applied to the muck improvement at the shield tunneling construction site of the connection passage. It is found that both the torque and thrust of the shield cutter head decrease significantly after the improvement of the soil layer at the site, and no mud cake is formed at the cutter head. The on-site construction is in a good state. The finite element method analysis shows that despite the increasing after the muck improvement，the ground settlement is relatively small.